Urban poverty response management during pandemic using geographic information system. Issue 1 (April 2021) - Hamim, S A; Usman, F; Gumano, H N; Jamil, F
Abstract: COVID-19 pandemic had influenced various aspects of community activities such as health, education and socio-economic. The effect of economic activities had caused many people to experience a decrease in income and loss of work due to the laid-off of informal workers. Overall, this unprecedented situation had led to an increase in the new poverty rate. In Palembang, based on the Non–DTKS (Integrated Social Welfare Data) data, the number of new poor affected by COVID-19 pandemic was 30, 765 people. Therefore, the new poor needed to be responded immediately, and the aid distribution needed to be followed up. This paper presents the development of a web-based operation dashboard in Geographic Information System to map the distribution of people categorized in poverty and new poor affected by the pandemic. The operational dashboard functioned as aid distribution activity monitoring. The type of aid, the number of people receiving the aid was recorded using the geo-tagging capabilities. By having this system, the community centres set up by the sub-district office would have an operational dashboard to monitor activities and examining the aid distribution.